2010
DOI: 10.1242/dev.051573
|View full text |Cite
|
Sign up to set email alerts
|

Mesoderm migration in Drosophila is a multi-step process requiring FGF signaling and integrin activity

Abstract: SUMMARYMigration is a complex, dynamic process that has largely been studied using qualitative or static approaches. As technology has improved, we can now take quantitative approaches towards understanding cell migration using in vivo imaging and tracking analyses. In this manner, we have established a four-step model of mesoderm migration during Drosophila gastrulation: (I) mesodermal tube formation, (II) collapse of the mesoderm, (III) dorsal migration and spreading and (IV) monolayer formation. Our data pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 56 publications
4
91
1
Order By: Relevance
“…Following invagination and an epithelial-to-mesechymal transition, a subset of deep mesodermal cells intercalate with more superficial cells that are in contact with the ectoderm (McMahon et al, 2010;McMahon et al, 2008;Murray and Saint, 2007). Radial intercalation of the deep cells depends on signaling by the FGF receptor heartless and its ligands Pyramus and Thisbe, which are all required for normal protrusion formation and intercalation (McMahon et al, 2010;Klingeisen et al, 2009;Murray and Saint, 2007). In our system, different isoforms of PDGF-A regulate both the intercalation of deep mesodermal cells and the directional migration of cells in contact with the BCR (current work and Nagel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Following invagination and an epithelial-to-mesechymal transition, a subset of deep mesodermal cells intercalate with more superficial cells that are in contact with the ectoderm (McMahon et al, 2010;McMahon et al, 2008;Murray and Saint, 2007). Radial intercalation of the deep cells depends on signaling by the FGF receptor heartless and its ligands Pyramus and Thisbe, which are all required for normal protrusion formation and intercalation (McMahon et al, 2010;Klingeisen et al, 2009;Murray and Saint, 2007). In our system, different isoforms of PDGF-A regulate both the intercalation of deep mesodermal cells and the directional migration of cells in contact with the BCR (current work and Nagel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Control of mesoderm cell behaviour by FGF It has been proposed that integrin-mediated contacts are responsible for high-affinity ME interactions in Drosophila (McMahon et al, 2010;Murray and Saint, 2007). b1-myospheroid (mys) integrin complexes become concentrated at the ME interface in the late stages of spreading (Leptin et al, 1989;McMahon et al, 2010).…”
Section: Research Articlementioning
confidence: 99%
“…b1-myospheroid (mys) integrin complexes become concentrated at the ME interface in the late stages of spreading (Leptin et al, 1989;McMahon et al, 2010). It has recently been reported that embryos maternally and zygotically (M/Z) mutant for the mys 1 allele exhibit defects in monolayer formation (McMahon et al, 2010).…”
Section: Research Articlementioning
confidence: 99%
“…During gastrulation, Htl FGFR-activation by either FGF ligands Pyramus (Pyr) or Thisbe (Ths) supports distinct as well as overlapping activities: Ths controls collapse of the invaginated mesodermal tube; both ligands are required to form a cell monolayer at the culmination of mesoderm spreading; and, following mesoderm spreading, Pyr predominantly supports differentiation of dorsal mesoderm lineages (Klingseisen et al, 2009;McMahon et al, 2010;Michelson et al, 1998). It does not appear that dedicated functions can be ascribed to a ligand for the course of development.…”
Section: Introductionmentioning
confidence: 99%